Situational analysis on capacity building among caregivers for the elderly: a case study in Ubon Ratchathani - Chanbunlawat, Khwanprapat; Chaiyasit, Yuttachai; Jitchan, Pensri (Science, Engineering and Health Studies, 2021)
Information on the situational analysis on capacity building among caregivers for the elderly has not been clearly explored. Therefore, a mixed method research, concurrent parallel design, was applied to this study. The participants were 384 caregivers and 20 key informants (caregivers) for elderly persons living in Ubon Ratchathani province, Thailand, in which the data were collected from August to December 2019. The research instruments included two questionnaires of the personal characteristics and situation of the elderly’s caregivers, as well as the capacity in caring of the elderly’s caregiver, and semi-structured questions. Both descriptive statistics and content analysis were used for data analysis. The research results revealed that the majority of the caregivers were female with a mean age of 49.42 years old, and had knowledge, skills and experience to care for elderly persons and had assistants. The duration of an individual being a caregiver was 11.64 years, and the amount of time of care was 13.02 h/day. Hypertension and diabetes mellitus were the common illnesses of the caregivers and the common physical health problems were back pain/waist pain/leg pain and fatigue. The overall score of the capacity in caring of the elderly’s caregiver was at the highest level. There were three ways for building the capacity in caring among caregivers for the elderly comprising promoting the knowledge of the caregivers, supporting from the government, and being employed as the elderly’s caregivers. The results of the study could be used for developing the capacity of the elderly’s caregivers and long-term care for the elderly people and their caregivers.